Faktor-Faktor Yang Berhubungan dengan Perilak Pemberian ASI Eksklusif Pada Bayi Usia 6-24 Bulan di Wilayah Kerja Puskesmas Sanggaran Agung Kabupaten Kerinci Provinsi Jambi - Moza Suzana (Malahayati Nursing Journal, 2022)
ABSTRACT: FACTORS RELATED TO EXCLUSIVE BREASTING BEHAVIOR IN INFANTS AGED 6-24 MONTHS IN THE WORK AREA OF SANGGARAN AGUNG PUSKESMAS, KEINCI REGENCY, JAMBI PROVINCE Introduction: The problem of exclusive breastfeeding in infants is caused by a lack of mother's knowledge, mother's attitude towards exclusive breastfeeding, busy working mothers, and low maternal education. In Indonesia, the exclusive breastfeeding coverage target is 80%, according to the 2013 Riskesdas report, the milk adequacy rate of 30.2% is still below the target.Objective: To determine the factors associated with exclusive breastfeeding behavior in infants aged 6-24 months in the Sanggaran Agung Community Health Center Work Area in 2020.Methods: This type of research is quantitative with a cross-sectional design. This research was conducted on August 2-10, 2020, with the population being all mothers with children under five in the Sanggaran Agung Health Center Work Area as many as 65 people, and samples were taken using the Total Population technique. Data was collected through a questionnaire sheet. Data were analyzed by univariate and bivariate with Chy Square test.Results: The results showed the frequency distribution of exclusive breastfeeding behavior (not giving exclusive breastfeeding 46.2%, exclusive breastfeeding 53.8%), knowledge factor (not good 41.5%, good 58.5%), place of delivery (non-health facilities) 30.8%, health facilities 69.2%), birth attendants (non-health workers 27.7%, health workers 72.3%), support from health workers (less supportive 44.6%, supported 55, 4%) and family support (less supportive 35.4%, supportive 64.6%).Conclusion: Based on the results of the study, it can be concluded that there is a relationship between knowledge of mothers, birthing places, birth attendants, support for health workers and family support with exclusive breastfeeding behavior for infants aged 6-24 months in the Sanggaran Agung Public Health Center, Kerinci Regency, Jambi Province in 2020. Support from health centers and related stakeholders to increase mother's knowledge about exclusive breastfeeding and provide support to mothers to be able to give exclusive breastfeeding to their babies. Keywords: Knowledge, place of delivery, birth attendant, support for health workers, family support, exclusive breastfeeding behavior  INTISARI: FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAK PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 6-24 BULAN DI WILAYAH KERJA PUSKESMAS SANGGARAN AGUNG KABUPATEN  KERINCI PROVINSI JAMBI Pendahuluan: Permasalah ASI eklusif pada bayi adalah karena pengetahuan ibu yang kurang, sikap ibu terhadap pemberian ASI eklusif, ibu sibuk kerja, pendidikan ibu yang rendah. Di Indonesia target cakupan ASI ekslusif adalah 80%, menurut laporan Riskesdas 2013, angka kecukupan ASI sebanyak 30,2% masih dibawah target.Tujuan: Tujuan penelitian ini untuk mengetahui faktor-faktor yang berhubungan dengan perilaku pemberian ASI Eksklusif pada bayi Usia 6-24 Bulan Di  Wilayah Kerja Puskesmas Sanggaran Agung Tahun 2020.Metode: Jenis penelitian ini adalah kuantitatif dengan desain Cross Sectional, Penelitian ini telah dilaksanakan pada tanggal 2-10 Agustus 2020, dengan populasi adalah semua ibu yang memiliki baduta di Wilayah Kerja Puskesmas Sanggaran Agung sebanyak 65 orang dan sampel diambil dengan teknik Total Populasi. Pengumpulan data dilakukan melalui lembar kuesioner. Data dianalisa secara univariat dan bivariat dengan Uji Chy Square.Hasil: Hasil penelitian didapatkan distribusi frekuensi Perilaku pemberian ASI Ekslusif (Tidak ASI Ekslusif 46,2%, ASI Ekslusif 53,8%), faktor pengetahuan (kurang baik 41,5%, Baik 58,5%), tempat persalinan (Non fasilitas kesehatan 30,8%, Fasilitas kesehatan 69,2%), penolong persalinan (non tenaga kesehatan 27,7%, tenaga kesehatan 72,3%), dukungan petugas kesehatan (kurang mendukung 44,6%, mendukung 55,4%) dan dukungan keluarga (kurang mendukung 35,4%, mendukung 64,6%).Kesimpulan: Berdasarkan hasil penelitian maka dapat disimpulkan bahwa Ada hubungan pengetahuan ibu, tempat persalinan, penolong persalinan, dukungan tenaga kesehatan dan dukungan keluarga dengan perilaku pemberian ASI eksklusif pada bayi usia 6-24 bulan di Wilayah Kerja Puskesmas Sanggaran Agung Tahun  Kabupaten Kerinci Provinsi Jambi 2020. Dukungan dari pihak puskesmas dan stakeholder terkait untuk dapat meningkatkan pengetahuan ibu tentang ASI Ekslusif serta memberikan dukungan bagi ibu untuk dapat memberikan ASI Ekslusif untuk bayinya. Kata Kunci :   Pengetahuan, tempat persalinan, penolong persalinan, dukungan tenaga kesehatan, dukungan keluarga, Perilaku Pemberian ASI Ekslusif